2019
DOI: 10.1080/17461391.2019.1633415
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of kinesio taping on muscular strength and endurance parameters of the finger flexors in sport climbing: A randomised, controlled crossover trial

Abstract: Kinesio taping (KT) is a commonly used intervention in sports and, recently, KT has become popular among athletes competing in sport climbing and bouldering events. However, evidence on the effect of KT on grip strength and endurance is still controversial. Therefore, the purpose of this study was to evaluate immediate effects of KT on muscular strength and endurance of the finger flexor muscles in sport climbers. Twenty recreationally-trained active sport climbers (10 men, 10 women) aged 28.5 ± 10.6 years per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
2
15
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to develop a low-cost and easy-to-build tool (i.e., MBboard) to assist in the evaluation of upper-limb strength in rock climbers. The MBboard was designed in order to meet the specific upper body muscular demand of rock climbing which has been characterized by high-intensity isometric contraction of the forearms combined with dynamic whole-body movements ( Limmer et al, 2019 ). Considering that there was no method universally accepted as gold standard for the measurement of maximal strength in rock climbers ( Michailov et al, 2018 ), previous studies have adopted the strategy to obtain construct validity evidence of field and laboratory tests by comparison between individuals with different rock climbing experience and/or by association with climbing ability self-reported by rock climbers ( Brent et al, 2009 ; Grant et al, 1996 ; López-Rivera and González-Badillo, 2019 ; Michailov et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to develop a low-cost and easy-to-build tool (i.e., MBboard) to assist in the evaluation of upper-limb strength in rock climbers. The MBboard was designed in order to meet the specific upper body muscular demand of rock climbing which has been characterized by high-intensity isometric contraction of the forearms combined with dynamic whole-body movements ( Limmer et al, 2019 ). Considering that there was no method universally accepted as gold standard for the measurement of maximal strength in rock climbers ( Michailov et al, 2018 ), previous studies have adopted the strategy to obtain construct validity evidence of field and laboratory tests by comparison between individuals with different rock climbing experience and/or by association with climbing ability self-reported by rock climbers ( Brent et al, 2009 ; Grant et al, 1996 ; López-Rivera and González-Badillo, 2019 ; Michailov et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence contradicts these directional techniques. [111][112][113][114] The survey focused on tape tension length only versus direc-tional strategies. Finally, this survey was sent to members of three professional organizations.…”
Section: Limitationsmentioning
confidence: 99%
“…Lee et al (12), Lemos et al (13), and Kouhzad Mohammadi et al (14) indicated an enormous increase in grip strength following the KT. While Chang et al (8), Limmer et al (15), and Zhang et al (16) declared that KT was not able to change hand grip. There is controversial evidence about the influence of KT on grip power (15,16).…”
Section: Introductionmentioning
confidence: 99%